The complete guide to the GATE:computer science engineering - Trishna Knowledge Systems (Pearson, 2013)
The complete guide to the GATE:computer science engineering / Trishna Knowledge Systems. -- New Delhi: Pearson, 2013 153.94004 T837 No. of Copies : 1